Réécritures d’un mythe et outils de détection des réutilisations. De l’Orphée de Virgile à celui de Ballanche - Karolina Suchecka; Nathalie Gasiglia (Humanités Numériques)
A corpus collecting rewritings of the myth of Orpheus and Eurydice allows us to study intertextuality and to represent it through a network of correspondences and within a comparative digital edition. For this purpose, we examine the output of two text reuse detection tools, TextPAIR and Tracer, in order to combine their treatments and exploit each one’s best potential. We propose a series of treatments to enrich the results and to overcome specific challenges observed. These technical manipulations allow us to interpret the results obtained for an essay by Pierre-Simon Ballanche and confront them with empirical analyses of the Orphic topos. Thus, we show that analysis supported by computational techniques is all the more useful for the study of intertextuality as it is adapted to the corpus.